2020
DOI: 10.1055/a-1300-1727
|View full text |Cite
|
Sign up to set email alerts
|

EFSUMB 2020 Proposal for a Contrast-Enhanced Ultrasound-Adapted Bosniak Cyst Categorization – Position Statement

Abstract: The well-established Bosniak renal cyst classification is based on contrast-enhanced computed tomography determining the malignant potential of cystic renal lesions. Ultrasound has not been incorporated into this pathway. However, the development of ultrasound contrast agents coupled with the superior resolution of ultrasound makes it possible to redefine the imaging of cystic renal lesions. In this position statement, an EFSUMB Expert Task Force reviews, analyzes, and describes the accumulated knowledge and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 89 publications
(209 reference statements)
3
59
0
3
Order By: Relevance
“…As proposed by other studies and by the EFSUMB Expert Task Force, the current CT-based classification scheme needs modification, while CEUS-based renal cystic criteria require validation, including histopathological correlation, in large prospective studies as a way to improve CEUS specificity and overall diagnostic performance. 23,24,29…”
Section: Discussionmentioning
confidence: 99%
“…As proposed by other studies and by the EFSUMB Expert Task Force, the current CT-based classification scheme needs modification, while CEUS-based renal cystic criteria require validation, including histopathological correlation, in large prospective studies as a way to improve CEUS specificity and overall diagnostic performance. 23,24,29…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction, the Bosniak classification system has helped radiologists stratify cystic renal lesions according to their risk of malignancy. While the Bosniak classification was originally developed for contrast-enhanced CT, the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) proposed a CEUS-adapted Bosniak categorization system in 2020 in order to overcome differences in imaging specifics and improve the diagnostic accuracy of CEUS in characterizing cystic renal lesions [33]. A recent study evaluating the impact of the updated Bosniak classification in MRI demonstrated higher interobserver agreement and higher diagnostic accuracy when using the updated version [34].…”
Section: Discussionmentioning
confidence: 99%
“…Hier werden die Läsionen nach der Applikation von Ultraschall-KM gemäß der CEUS-Bosniak-Klassifikation eingeteilt, die dabei hilft, harmlose Zysten (CEUS-Bosniak I bis II) bzw. eher harmlosere (CEUS-Bosniak-IIF) sicher als solche zu identifizieren und die potenziell suspekten Befunde (CEUS-Bosniak III und IV), meist nach einer KM-basierten Computertomographie(CT)oder Magnetresonanztomographie(MRT)-Untersuchung, in einem Nierentumorboard interdisziplinär zu diskutieren ( [24]; Abb. 7).…”
Section: Ultraschall Bei Unklaren Nierenläsionenunclassified